2019
DOI: 10.1038/s41564-019-0407-8
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Enterobacteriaceae underlie variation in susceptibility to Salmonella infection

Abstract: SUMMARY PARAGRAPH Lack of reproducibility is a prominent problem in biomedical research. An important source of variation in animal experiments is the microbiome, but little is known about specific changes in the microbiota composition that cause phenotypic differences. Here we show that genetically similar laboratory mice obtained from four different commercial vendors exhibited marked phenotypic variation in their susceptibility to Salmonella infection. Fecal microbiota transplantation into germ-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
167
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(178 citation statements)
references
References 31 publications
10
167
0
1
Order By: Relevance
“…134,168,195,209 When known, relevant genetic variants exist, for example, in metabolism, specimens for genetic analyses should at least be collected and saved. • Age, sex, race/ethnicity, body size and composition, health status (especially with respect to outcomes of interest), co-medications, smoking, geography.…”
Section: Post-trial Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…134,168,195,209 When known, relevant genetic variants exist, for example, in metabolism, specimens for genetic analyses should at least be collected and saved. • Age, sex, race/ethnicity, body size and composition, health status (especially with respect to outcomes of interest), co-medications, smoking, geography.…”
Section: Post-trial Interpretation Of Resultsmentioning
confidence: 99%
“…190,191 These effects are modulated by sex in organisms ranging from fish and mice through humans. 168 Good practices for characterization of the gut microbiota have been discussed elsewhere. In addition, changes in the gut microbiota may exert separate direct or indirect effects on animal biology and health.…”
Section: Model-and Context-related Considerationsmentioning
confidence: 99%
“…For example, animals of the same strain, but from different sources, or animals obtained from the same source but at different times, may be genetically different [17]. The immune or microbiological status of the animals can also influence welfare, experimental variability and scientific outcomes [106][107][108].…”
Section: Explanationmentioning
confidence: 99%
“…Exposure to antibiotics was not associated with Kp colonization or subsequent infection in our intensive care unit patient population 1,18 , indicating that Kp must contend with the indigenous microbiota to colonize the gut and cause infection. Previous studies have shown that gut microbiota differs by mouse vendor and by the room within each vendor facility (referred to as "barrier") 19 and these differences can impact experimental output [20][21][22] . Therefore, C57BL/6J mice were sourced from two different barriers (RB16 and RB07) at The Jackson Laboratory and inoculated orally with a mixture of wild-type and terC Kp (Fig.…”
mentioning
confidence: 99%